Conhecimentos e atitudes de pais e de professores diante do transtorno específico de aprendizagem com foco na dislexia: adaptação de instrumento - Ana Paula Rocha (2023)
Child development must be understood comprehensively, considering physical, social, emotional, cognitive and behavioral factors. Identifying problems in any of these areas early is crucial to minimizing learning difficulties. This Master's Thesis is characterized by two studies with an exploratory and applied methodology, with development in transversal time. Study 1 aimed to develop the initial steps for the development of an instrument to evaluate and measure the knowledge and attitude of parents and teachers towards Specific Learning Disorder (TEAp), with a focus on dyslexia. The questions (and their respective items) of this instrument were constructed from a mix of the versions for parents and teachers of the Questionnaire on Specific Learning Disorder (EHTF, 2010), respectively translated and adapted into Portuguese and the Brazilian context by Braga (2020) and De Paula (2019). In this process, overlapping information was eliminated and questions and items considered not relevant to the proposal to develop an instrument aimed at dyslexia and that served two audiences: parents and teachers, were excluded. In parallel, based on the deepening of the bibliography on dyslexia and the impact of the COVID-19 pandemic on learning, new questions and items were added to the new instrument. The result of Study 1 was the compilation of the instrument entitled Questionnaire for parents and teachers – Pre-analysis version by judges. This initial version, consisting of 17 questions and 124 items, represents the first step in the development of the final instrument Questionnaire on the knowledge and attitudes of parents and educators about dyslexia, to be completed in subsequent studies. Study 2 aimed to provide evidence of initial content validity of the instrument created in Study 1, which was submitted to nine expert judges. Despite the limitations discussed, in general, there was agreement among the judges regarding the relevance of the instrument with regard to measuring the knowledge of parents and teachers about Dyslexia. Based on the feedback received, the instrument will be improved and submitted to both the target population and new judges. After these procedures, future research should also be conducted to explore other sources of psychometric evidence of reliability and validity for the Questionnaire on the knowledge and attitudes of parents and educators about dyslexia.